Evaluation of Ready to Use Flavoured Drink Prepared with Camel Milk Powder - Tanwar, Anita; Berwal, Raj Kumar; Kumar, Yogesh; Harsh, Anil; Masar, Priyanka; Godara, Kapil Kumar; Choudhary, Vimala; Kumar, Sandeep; Kalla, Yamini; Parerna, (International Journal of Bio-resource and Stress Management, 2025)
Experiment was conducted from June, 2023 to December, 2024 for PhD research work at ICAR-National research Centre on Camel, Bikaner, Rajasthan, India to prepare a healthy drink with freeze-dried camel milk powder. The Flavoured drink was prepared with the help of freeze-dried camel milk powder and cardamom powder with powdered sugar at different levels. Camel milk was procured from NRCC, and freeze-dried with the help of freeze-drier. The chemical composition of raw camel milk was as Fat-3%, SNF-6.23%, Acidity- 0.129, Protein-2.5%, Lactose-3.65%, and total solid was found 7.75%. The freeze-dried camel milk powder was dissolved in water with different levels of cardamom powder. The three levels of cardamom powder i.e. 0.2%, 0.5% and 1% were incorporated and 0.5% cardamom powder and 6% sugar was optimized based of sensory evaluation and physio-chemical parameters. Thus 0.5% level was chosen based of sensory attributes. The following observation were noted as Moisture-0.5%, Fat-15.08±0.60%, Protein-20.03±0.57%, Ash-6.28±0.09%, Loose bulk density-0.29±0.01, tapped bulk density-0.90±0.07. Particle size of camel milk powder were D [3, 2] 2.19 µm D [4, 3] 4.15 µmDv (10) 1.05 µmDv (50) 2.97 µmDv (90)7.92 µmand instant flavoured drink powder is D [3, 2] 2.21 µm D [4, 3] 4.34 µmDv (10) 1.05 µmDv (50) 3.01 µmDv (90) 8.18 µm. Total plate counts (TPC)and yeast and mold counts (YMC) increased significantly (p<0.05) from day o to 180 days of storage in FDCMP and as well as IFDP. A significant (p<0.05) effect of addition of cardamom powder and sugar powder showed significantly (p<0.05) lower TPC and YMC during entire period of storage.